MUTAGENICIDADE DO EXTRATO DE CASCA DE Musa paradisiaca (MUSACEAE) EM CÉLULAS DE SANGUE PERIFÉRICO DE CAMUNDONGOS IN VIVO - Andrade, Cláudia Umbelina Baptista (2007)
Plants are a source of many biologically active products and nowadays they are of great interest to the pharmaceutical industry. In the present study, the mutagenic potential of the fruit peels extract from Musa paradisiaca was assessed using the single cell gel electrophoresis (Comet assay) and micronucleus assays. Animals were treated orally with three different concentrations of the extract (1000, 1500 and 2000 mg/kg of body weight). Peripheral blood cells of Swiss mice were collected 24 h after the treatment for the comet assay and 48 and 72 h for the micronucleus test. The results showed that the extract of M. paradisiaca induced statistically significant increases in the average numbers of DNA damage in peripheral blood leukocytes for the two higher doses and a significant increase in the mean of the micronucleated polychromatic erythrocytes at three tested doses. The polychromatic/normochromatic erythrocytes ratio (PCE/NCE) scored in the tested groups was not statistically different from the negative control, showing that the extract presented no cytotoxic effects. The data obtained indicate that fruit peels extract from M. paradisiaca showed mutagenic effect in the peripheral blood cells of Swiss albino mice.